Characterization and Analysis of Ultrathin CIGS Films and Solar Cells Deposited by 3-Stage Process - Grace Rajan; Krishna Aryal; Shankar Karki; Puruswottam Aryal; Robert W. Collins; Sylvain Marsillac (Journal of Spectroscopy)
In view of the large-scale utilization of Cu(In,Ga)Se2 (CIGS) solar cells for photovoltaic application, it is of interest not only to enhance the conversion efficiency but also to reduce the thickness of the CIGS absorber layer in order to reduce the cost and improve the solar cell manufacturing throughput. In situ and real-time spectroscopic ellipsometry (RTSE) has been used conjointly with ex situ characterizations to understand the properties of ultrathin CIGS films. This enables monitoring the growth process, analyzing the optical properties of the CIGS films during deposition, and extracting composition, film thickness, grain size, and surface roughness which can be corroborated with ex situ measurements. The fabricated devices were characterized using current voltage and quantum efficiency measurements and modeled using a 1-dimensional solar cell device simulator. An analysis of the diode parameters indicates that the efficiency of the thinnest cells was restricted not only by limited light absorption, as expected, but also by a low fill factor and open-circuit voltage, explained by an increased series resistance, reverse saturation current, and diode quality factor, associated with an increased trap density.